COVERAGE OF THE BUKHARA EMIRATE DURING THE REIGN OF AMIR NASRULLOH IN CONTEMPORARY SOURCES (International journal of artificial intelligence, 2025)
This study analyzes sources that illuminate the social, political, and cultural life of the Bukhara Emirate during the reign of Amir Nasrullah (1860-1885). Amir Nasrullah, in his policy, sought to preserve the independence of the Bukhara Emirate, while simultaneously introducing elements of modernization.